Users' perceptions of e-learning environments and services effectiveness: The emergence of the concept functionality model. Issue 1 (12th February 2018) - Haq, Anwar ul; Magoulas, George; Jamal, Arshad; Majeed, Asim; Sloan, Diane
Abstract : Purpose: E-learning environments and services (ELES) adoption and success rates challenge ELES designers, practitioners and organisations. Enterprise decision makers continue to seek effective instruments in launching such systems. The purpose of this paper is to understand users' perceptions of ELES effectiveness and develop a theoretical framework which improves understanding of success factors for adoption. Design/methodology/approach: Grounded theory method is used to reflect on the relationships between changing users' requirements and expectations, technological advances and ELES effectiveness models. A longitudinal study collecting data from social media blogs over four years was authenticated based on the context evaluation, language structure and conversational constructs. Findings: Identification of a new core dimension named "Concept Functionality" which can be used to understand the relationships between e-learning effectiveness factors including the relationships with other domains such as security. The findings are also used to validate major existing models for the success of ELES. Practical implications: The new framework potentially improves system design process in the fields of education technology, enterprise systems, etc. Originality/value: Concept functionality dimension can offer more insights to understand ELES effectiveness and further improve system design process in a variety of domains including enterprise systems, process modelling and education technology.